Penerapan Model DeLone & McLean dalam Menilai Kesuksesan dan Kapabilitas Pengguna Sistem Informasi di Industri Logistik - Rivera, Farel Brahmantyah; Wulansari, Anita; Safitri, Eristya Maya (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The Integrated Depot Management System is an integrated information system developed at PT. Masaji Tatanan Kontainer Indonesia as the primary platform for the company's operational and marketing activities aimed at achieving competitive advantage, adapting to the market, and achieving significant improvement through consistency, creativity, and innovation. This research aims to evaluate the success of the Integrated Depot Management System application using the DeLone & McLean Success Model. This study adapts 6 main variables from D&M: Service Quality, System Quality, Information Quality, User Satisfaction, Intention to Use, and Net Benefits, integrating the external variable User Capability with data processing techniques using SEM-PLS. Fourteen hypotheses were formulated to evaluate the relationships among the developed success dimensions. Of the 14 proposed hypotheses, nine were accepted and five were rejected. The findings indicate that the Integrated Depot Management System requires development in terms of quality, starting from system quality, service, and the quality of information provided. This development is necessary to achieve user desires and satisfaction in using the application to fulfill the company's vision and mission.